Near-infrared spectroscopy–guided personalized repetitive transcranial magnetic stimulation for bipolar depression: a case report - Chun-Hung Chang; Chun-Hung Chang; Chun-Hung Chang; Wen-Chun Liu; Po-Han Chou (Frontiers in Psychiatry)
IntroductionTranscranial magnetic stimulation (TMS) is a common treatment for depression, particularly in patients unresponsive to conventional therapies. High-frequency (10 Hz), low-frequency (1 Hz), or bilateral (left, high-frequency; right, low-frequency) stimulation of the dorsolateral prefrontal cortex (DLPFC) has been demonstrated to be effective in studies based on prefrontal asymmetry theory, which suggests that depression is associated with reduced left frontal function and increased right frontal function. However, few reliable predictors or biomarkers are available for personalizing treatment protocols on the basis of a patient’s brain function. Near-infrared spectroscopy (NIRS), a noninvasive neuroimaging tool that assesses functional changes in the brain during cognitive tasks, can measure a patient’s bilateral frontal lobe function in real time. Thus, this tool can aid the development of personalized TMS protocols for patients with depression.MethodsA 19-year-old woman presented to our psychiatric clinic with bipolar depression. NIRS was performed to select an appropriate TMS protocol for the patient. A verbal fluency test revealed bilateral low frontal lobe function. Thus, we selected a TMS protocol involving 10 sessions of bilateral high-frequency stimulation over 4 days, with each session delivering 3000 pulses on each side of the DLPFC.ResultsBefore treatment, the patient’s scores on the Hamilton Depression Rating Scale (HAMD), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Young Mania Rating Scale were 40, 57, 40, and 6, respectively. After treatment, her depressive symptoms substantially improved, with HAMD, BDI, and BAI scores decreasing to 17, 21, and 14, respectively. Although the treatment led to side effects such as dizziness and headache, these effects resolved after the treatment. At the 6-month follow-up, the patient’s condition was still stable, with HAMD, BDI, and BAI scores of 10, 13, and 7, respectively.ConclusionOur case suggests that NIRS can guide the selection of appropriate TMS protocols for patients with bipolar depression. Although our findings are promising, further randomized controlled trials are needed to validate the efficacy and safety of and determine the optimal parameters for this approach.